Kebijakan dan Implementasi Pemberian Hak atas Tanah Untuk Saluran Udara Tegangan Tinggi (SUTT) Berdasarkan Undang-undang Pokok Agraria - agus, I Ketut Agus Suarnata; nani, Qadriani Arifuddin (Universitas Islam DDI AG.H. Abdurrahman Ambo Dalle, 2025)
The granting of land rights for the construction of High Voltage Overhead Transmission Lines (SUTT) is a manifestation of the implementation of the state's right to control land as regulated in Article 2 of the Basic Agrarian Law (UUPA) of 1960. This policy aims to support the provision of national electrical infrastructure for the public interest. The latest implementing regulation, namely the Minister of Energy and Mineral Resources (ESDM) Regulation Number 13 of 2021, regulates the free space and minimum distance of the electricity transmission network, including the compensation mechanism for landowners whose activities are restricted by the presence of SUTT. In its implementation, although land ownership remains in the hands of the community, the use of free space is limited to ensure the safety and reliability of the transmission network. Due to these restrictions, landowners are entitled to receive compensation as a form of appreciation for the rights that are limited. The purpose of writing this scientific paper is to discuss how land consolidation is implemented in spatial planning, as well as the benefits of land consolidation in Indonesia. The method used in this scientific paper is normative juridical.